KEPUTUSAN INVESTASI, KEPUTUSAN PENDANAAN, DAN KEBIJAKAN DIVIDEN TERHADAP NILAI PERUSAHAAN MANUFAKTUR - Astuti Yuli Setyani; Ambar Kusuma Astuti (Fakultas Bisnis UKDW, 2014)
The purpose of this study was toexamine the effect of investment decisions, financing decisions and dividend policy on firm value. The sample in this study is a manufacturing company established on criteria. Data were obtained from the Indonesian Capital Market Directory (ICMB) and the manufacturing company's financial statement since the period 2008-2011. Based on purposive sampling method, samples obtained by 158 observations. Regression analysis done based on the results of the data analysis. The hypothesis in this study were tested using multiple regression analysis. This study concludes some of the following: (1) variable dividend policy was not shown to affect the value of the company, (2) variable funding decisions variable shown to affect tthe value of the company,(3) investment decision variables was not shown to affect tthe value of the company. Keywords: investment decisions, financingdecisions, dividend policy, the value ofthe company